Short-Term Clinical Results of Ab Interno Trabeculotomy Using the Trabectome with or without Cataract Surgery for Open-Angle Glaucoma Patients of High Intraocular Pressure - Handan Akil; Vikas Chopra; Alex S. Huang; Ramya Swamy; Brian A. Francis (Journal of Ophthalmology)
Purpose. To assess the safety and efficacy of Trabectome procedure in patients with preoperative intraocular pressure (IOP) of 30 mmHg or higher. Methods. All patients who had underwent Trabectome stand-alone or Trabectome combined with phacoemulsification were included. Survival analysis was performed by using Kaplan-Meier, and success was defined as IOP ≤ 21 mmHg, 20% or more IOP reduction from baseline for any two consecutive visits after 3 months, and no secondary glaucoma surgery. Results. A total of 49 cases were included with an average age of 66 (range: 13–91). 28 cases had Trabectome stand-alone and 21 cases had Trabectome combined with phacoemulsification. Mean IOP was reduced from a baseline of 35.6 ± 6.3 mmHg to 16.8 ± 3.8 mmHg at 12 months (p<0.01∗), while the number of medications was reduced from 3.1 ± 1.3 to 1.8 ± 1.4 (p<0.01∗). Survival rate at 12 months was 80%. 9 cases required secondary glaucoma surgery, and 1 case was reported with hypotony at day one, but resolved within one week. Conclusion. Trabectome seems to be safe and effective in patients with preoperative IOP of 30 mmHg or greater. Even in this cohort with high preoperative IOP, the end result is a mean IOP in the physiologic range.